Quinn - Johansen, Iris. (New York : St. Martin's Press, 2011)
A former Navy Seals member turned cop falls in love with a woman in need of his help and finds himself in the cross hairs of danger.
Keywords: Police -- Fiction; Duncan, Eve (Fictitious character) -- Fiction; Women intelligence officers -- Fiction; Missing persons -- Fiction; Romantic suspense fiction; Mystery fiction